Collaboration Towards A Sustainable Halal Industry Ecosystem: Pentahelix Approach - Alfianto, Achmad Nur (Jurnal Ekonomi, Akutansi dan Manajemen Nusantara, 2025)
Abstract− Indonesia continues to make significant strides toward becoming a key player in the global halal industry. Although the country possesses vast potential in this sector, the overall performance of the halal industry still faces various challenges and requires further enhancement. To realize this potential, strong and inclusive collaboration among all stakeholders is crucial in ensuring the long-term sustainability and global competitiveness of Indonesia’s halal ecosystem. This study seeks to explore and understand the roles of various stakeholders, namely the government, academics, business actors, media, and community groups in supporting the development of the halal supply chain in Indonesia. Using the Pentahelix model as a framework, this research emphasizes the importance of multi-stakeholder collaboration in building a robust and inclusive halal industry. Employing a qualitative descriptive approach through library research, the study reveals that each stakeholder within the Pentahelix framework holds a vital and strategic role in advancing the halal industry. The findings highlight the need for integrated and synergistic efforts among all parties to foster a sustainable halal ecosystem. Key challenges identified include the necessity for effective communication and coordination among stakeholders, as well as the need to leverage technological innovations in the halal supply chain.